2012
DOI: 10.1088/1674-1056/21/9/096101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of defect states on band gaps in the two-dimensional phononic crystal of 4340 steel in an epoxy

Abstract: The band structures of a new two-dimensional triangle-shaped array geometry of 4340 steel cylinders of square cross section in an epoxy resin were studied by the plane-wave expansion and supercell calculation method. The band gaps of this type of phononic crystals with different defects were calculated such as defect-free, 60 • crystal linear defect states, 120 • crystal linear defect states, and 180 • crystal linear defect states. It was found that the band gap will emerge in different linear defects of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…In addition, it is noted that the filter is robust and topological protected, which is distinct from the ordinary defects. [55,56] Simulated results are given in Appendix B. This significant property to freely adjust the bandwidth of the edge states provides excellent ways for the design of adjustable topological acoustic materials.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is noted that the filter is robust and topological protected, which is distinct from the ordinary defects. [55,56] Simulated results are given in Appendix B. This significant property to freely adjust the bandwidth of the edge states provides excellent ways for the design of adjustable topological acoustic materials.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] As a functional material with periodic structure, PC is also composed of two kinds of materials, and because of their band gap and passband characteristics, in recent years, many scholars have studied their applications in noise reduction and vibration reduction of acoustic transducers. [11][12][13][14] Kong et al [15] and Ahmed et al [16] have shown that the existence and width of a complete band gap can be adjusted by adding a defect state into the PC structure, thereby changing the filling rate of the scatterer, the temperature, etc. Based on their bandgap characteristics, the PCs have been widely used in vibration suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials have been implemented by using artificial crystal structures for a wide range of wave spectra. Photonic crystals, [1][2][3][4][5][6][7][8][9][10][11][12] phononic crystals, [13][14][15][16][17][18][19][20][21][22][23] and sonic crystals [24][25][26][27][28] were developed for their technological potentials such as wave focusing, [24][25][26][27][28][29][30][31] wave isolation, [16][17][18]21] wave absorption, [10,22] and wave guiding. [2][3][4]32,33] The realization of flat lenses from crystal structures is one of the promising applications of metamaterials.…”
Section: Introductionmentioning
confidence: 99%